Non-pathogenic microbiota accelerate age-related CpG Island methylation in colonic mucosa. Issue 1 (31st December 2023) - Sun, Ang; Park, Pyounghwa; Cole, Lauren; Vaidya, Himani; Maegawa, Shinji; Keith, Kelsey; Calendo, Gennaro; Madzo, Jozef; Jelinek, Jaroslav; Jobin, Christian; Issa, Jean-Pierre J.
ABSTRACT: DNA methylation is an epigenetic process altered in cancer and ageing. Age-related methylation drift can be used to estimate lifespan and can be influenced by extrinsic factors such as diet. Here, we report that non-pathogenic microbiota accelerate age-related methylation drift in the colon when compared with germ-free mice. DNA methylation analyses showed that microbiota and IL10KO were associated with changes in 5% and 4.1% of CpG sites, while mice with both factors had 18% alterations. Microbiota, IL10KO, and their combination altered 0.4%, 0.4%, and 4% of CpG island methylation, respectively. These are comparable to what is seen in colon cancer. Ageing changes were accelerated in the IL10KO mice with microbiota, and the affected genes were more likely to be altered in colon cancer. Thus, the microbiota affect DNA methylation of the colon in patterns reminiscent of what is observed in ageing and colorectal cancer.